2019
DOI: 10.1109/lmag.2019.2908149
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Localization for an Electromagnetic-Based Haptic Interface

Abstract: In this letter, we develop a magnetic localization system for an electromagnetic-based haptic interface (EHI). Haptic interaction is achieved using a controlled magnetic force applied via an EHI on a magnetic dipole attached to a wearable finger splint. The position of the magnetic dipole is estimated using two identical arrays of three-dimensional magnetic field sensors in order to eliminate the magnetic field generated by the EHI. The measurements of these arrays are used to estimate the position of the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…There are primarily two types of magnetic sources for spatial localization, that is, solenoid coils 14,15 and permanent magnets. [16][17][18][19] Su et al introduced AMagPoseNet, an end-to-end neural network model designed to tackle the inverse static magnetic problem. 20 Chen et al designed a MagX sensor matrix for the positioning of wearable spherical magnets.…”
Section: Related Workmentioning
confidence: 99%
“…There are primarily two types of magnetic sources for spatial localization, that is, solenoid coils 14,15 and permanent magnets. [16][17][18][19] Su et al introduced AMagPoseNet, an end-to-end neural network model designed to tackle the inverse static magnetic problem. 20 Chen et al designed a MagX sensor matrix for the positioning of wearable spherical magnets.…”
Section: Related Workmentioning
confidence: 99%
“…The shortcoming of passive magnets can be addressed using electromagnetism and computational control of magnetic forces. Two-dimensional arrays of electromagnets can be combined with passive magnets that are worn [58,63,60,2,8,6,9] or embedded in tools and interactive objects [28,43,57]. The actuation area can be increased by attaching an electromagnet to a biaxial linear stage [32,33].…”
Section: Electromagnetic Haptic Feedbackmentioning
confidence: 99%
“…2. Position of helical robot is localized during its propulsion inside a catheter segment under the influence of rotating magnetic fields [13]. (a) Position is measured and estimated using camera feedback and a magnetic localization system, respectively.…”
Section: A Characterization Inside Whole Bloodmentioning
confidence: 99%
“…approval(2018-06-PBT-NH) is obtained for the collection and handling of the sample, and the donor has given written informed consent. An array of Hall-effect sensors is used to localize the helical robot and measure its speed as the robot is not visible in blood [13]. A representative trial for the localization of the helical robot in PBS is shown in Fig.…”
Section: A Characterization Inside Whole Bloodmentioning
confidence: 99%